2017
DOI: 10.1111/jth.13778
|View full text |Cite
|
Sign up to set email alerts
|

A fusion protein of interleukin‐4 and interleukin‐10 protects against blood‐induced cartilage damage in vitro and in vivo

Abstract: Background Joint damage still causes significant morbidity in hemophilia. It results from synovial inflammation and direct cartilage-degenerating properties of blood components. Interleukin (IL)-4 and IL-10 have been shown to protect cartilage from blood-induced damage. Recently an IL4-10 fusion protein has been developed to combine the function of IL-4 and IL-10 and increase their bioavailability. Objectives In this study we evaluate whether this IL4-10 fusion protein protects against blood-induced joint dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…On the other hand, cartilage degeneration was not observed. This aligns with previous findings and the fact that cartilage degeneration has been shown to be more pronounced in this model following two induced joint bleeds …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, cartilage degeneration was not observed. This aligns with previous findings and the fact that cartilage degeneration has been shown to be more pronounced in this model following two induced joint bleeds …”
Section: Discussionsupporting
confidence: 93%
“…This aligns with previous findings and the fact that cartilage degeneration has been shown to be more pronounced in this model following two induced joint bleeds. 16,35 Our findings substantially add to the value of this model, from which important knowledge on HA has been gained previously. 8 The observed variability in bleeding volume could reflect an exaggerated view of the clinical situation where "clinically evident joint bleeds" range from clinically unconfirmed joint bleeds based on the patients' experience all the way to the largest joint bleeds.…”
Section: Discussionsupporting
confidence: 61%
“…Nasal administration of neutralizing anti-IL-10 antibody and recombinant IL-10 Thirty min before antibody or recombinant IL-10 fusion of human IL-10 and human IL-4 connected via a linker sequence to increase its stability [36][37][38], A concentration of 3 µl of hyaluronidase (total 100 U; Sigma-Aldrich) in PBS was delivered to each nostril [39]. c The tail-suspension test (TST) was performed in WT and Rag1 −/− mice at 24 h postinjection (n = 7 mice/group).…”
Section: Methodsmentioning
confidence: 99%
“…Pro-inflammatory cytokines have been reported to be involved in the pathogenesis of synovitis [25,28] as interactions within the cytokine network and other inflammatory mediators in the affected joint can create an inflammatory environment. Theoretically, an anti-cytokine approach can be used to protect against bleeding in damaged joints; however, limited studies have shown that intervention of the cytokine network may serve as a novel therapeutic direction [5,[29][30][31]; this includes our previous study with anti-IL-6 in hemophilia A mice [8].…”
Section: Discussionmentioning
confidence: 99%